2009
DOI: 10.1097/tp.0b013e3181a5e5f1
|View full text |Cite
|
Sign up to set email alerts
|

MELD Score and Blood Product Requirements During Liver Transplantation: No Link

Abstract: In this series, the MELD score was as high as US series and did not predict blood losses and blood product requirement during liver transplantation. If the MELD system has to be implemented to prioritize orthotopic liver transplantation, it should be revisited, and the starting hemoglobin value should be added to the equation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
52
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(59 citation statements)
references
References 38 publications
6
52
1
Order By: Relevance
“…These complications are caused mainly by massive haemorrhage and the pathophysiological features of the anhepatic stage, including the clamping of the great vessels and the congestion of internal organs. Similarly, a previous study by Massicotte et al,10 demonstrated no difference in the volume of bleeding during surgery and the volume of blood components transfused between two groups, divided based on the median MELD score value (21 points). The relationship between MELD score and transfusion requirements during liver transplantation is controversial.…”
Section: Discussionmentioning
confidence: 99%
“…These complications are caused mainly by massive haemorrhage and the pathophysiological features of the anhepatic stage, including the clamping of the great vessels and the congestion of internal organs. Similarly, a previous study by Massicotte et al,10 demonstrated no difference in the volume of bleeding during surgery and the volume of blood components transfused between two groups, divided based on the median MELD score value (21 points). The relationship between MELD score and transfusion requirements during liver transplantation is controversial.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, the extent of the coagulopathy or the severity of liver failure as assessed by the model of end-stage liver disease (MELD) score does not predict the proportion of patients who do require perioperative transfusion. 80 We believe that a major surgical procedure such as liver transplantation would never be possible in a patient with a true coagulopathic state, such as a patient with hemophilia, without correction of the coagulopathy with factor concentrates or blood product transfusion. (B and table), concomitant changes in pro-and antihemostatic pathways result in a "rebalance" in the hemostatic system.…”
Section: Clinical Evidence For Rebalanced Hemostasis In Liver Diseasementioning
confidence: 99%
“…In addition, the impact of the severity of the disease assessed with the Child-Pugh score and Model of End-Stage Liver Disease (MELD) score was frequently studied, yielding inconsistent results. Although Mangus et al [20] have suggested that the MELD score is an independent predictor of intraoperative blood loss, as well as the number of RBCs transfused, this has not been confirmed in subsequent studies [21]. Interestingly, Roullet et al have demonstrated that the Child-Pugh class, but not MELD score is an independent predictor of transfusion requirements [22].…”
Section: Recipient-related Predictors Of Blood Transfusionmentioning
confidence: 89%